Higher education funding reforms: a comprehensive analysis of educational and labour market outcomes in England - Azmat, Ghazala; Simion, Stefania (London, 2018)
"This paper investigates the impact of changes in the funding of higher education in England on students’ choices and outcomes. Over the last two decades – through three major reforms in 1998, 2006 and 2012 – undergraduate university education in public universities moved from being free to students and state funded to charging substantial tuition fees to all students. This was done in conjunction with the government offering generous means-tested maintenance grants and loans. Using detailed longitudinal micro-data that follows all students attending state schools in England (more than 90 percent of all school-aged children) from lower education to higher education, we document the socio-economic distributional effects of the 2006 and 2012 policy reforms on a comprehensive set of outcomes, including enrolment, relocation decisions, selection of institution, program of study, and performance within university. For a subset of students, we track them after completing higher education, allowing us to study the labour market effects of the policy reforms. Despite the substantial higher education funding reforms, we do not find large aggregate effect on student enrolment or on other margins. Moreover, the small negative impacts found on enrolment were largely borne on those in higher parts of the wealth distribution – reducing the enrolment gap across socioeconomic groups. "